Struktur Jaringan dan Mekanisme Distribusi Benih Unggul melalui Analisis Jejaring Sosial: Perspektif Petani Jagung di Kabupaten Garut - Ditanisa Amira Silitonga; Zumi Saidah; Eliana Wulandari (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2026)
Maize is a strategic agricultural commodity used both as a food source and as a major component of animal feed, making increased production increasingly important. One way to improve maize productivity is to use superior maize seeds. However, farmers’ access to these seeds remains uneven due to constraints in the distribution system. This study analyzes the social network structure of the maize seed distribution system and identifies the key actors influencing farmers’ access to seeds, information, and solutions. Using a Social Network Analysis (SNA) approach with an ego-network perspective, the study was conducted in two maize-producing sub-districts in Garut Regency and involved 100 farmers selected through stratified random sampling. Data were collected through questionnaires and analyzed using Gephi 0.10. The results show that the seed distribution network is direct, heterogeneous, and relatively sparse, with farmers connected mainly to specific central actors rather than through intermediary channels. Farm shops, fellow farmers, and government assistance programmes occupy dominant positions in the network, indicating the importance of market-based mechanisms, informal farmer networks, and state support in shaping seed access. In contrast, local institutional actors, particularly cooperatives and farmer groups, have not played an optimal role in the distribution network. These findings suggest that improving farmers’ access to superior maize seeds requires strengthening local farmer institutions, increasing coordination among distribution actors, and reducing dependence on a limited number of dominant actors.